"This is not a nice safe space": investigating women's safety work on Tinder. Issue 1 (2nd January 2023) - Gillett, Rosalie
ABSTRACT: As dating app use continues to rise, so too do women's experiences of intrusion in digital dating contexts. The extent to which dating apps facilitate intimate intrusions—defined in this article as behaviour that makes women feel uneasy, uncomfortable, or unsafe—has been the subject of burgeoning scholarly and media attention. While this research provides important evidence for the range of intrusions women experience on dating apps, to date, little is known about how women protect themselves in digital dating contexts. Drawing on qualitative interview and walkthrough data, this research investigated the strategies women employ to protect themselves—referred to throughout this paper as "safety work"—from men's intrusive behaviour on the dating app Tinder. Findings from this paper demonstrate the range of online and offline strategies women employ to respond to, avoid, and cope with men's violence. Given the burden placed on women to protect themselves, this paper argues that women's safety work limits their ability to participate freely on dating apps.